A atuação do Ministério Público diante do conflito entre o direito à moradia e o direito ao meio ambiente, nas áreas de Preservação Permanente Urbanas em Cáceres-MT - SALDANHA, Evely Bocardi de Miranda (Universidade Federal do Pará, 2018)
The present paper analyses the proceedings of the Public Prosecutor's Office towards the conflict between the right to housing and the right to an ecologically balanced environment in the case of the occupation of the Empa neighborhood, in the city of Cáceres in Mato Grosso, an urban area of permanent preservation. Due to the housing deficit and the shortage of urban planning, the low-income population is forced to irregularly occupy peripheral locations of minor importance and of less value in the city, areas of risk or of environmental preservation, where they live and survive without basic conditions of sanitation or infrastructure. Consequently it is necessary that Public Authorities develop policies of urban development to facilitate access to decent and adequate housing, in a balanced and preserved urban environment for present and future generations, ensuring the full development of the social functions of the city, the well-being and healthy quality of life of its inhabitants, since the right to housing and to an ecologically balanced environment are inherent and essential to every human being in order to ensure an adequate standard of living. For such, the Public Prosecutor's Office is a key character in the supervision and implementation of public policies that guarantee the rights to the city to its inhabitants. Therefore, it’s a case study of the occupation process, municipal urbanization, particularly in the Empa neighborhood and the challenges faced in order to achieve the right to the city.